Estudo da expressão das proteínas Twist1, Kai1 e E-Caderina em amostras de câncer de pênis, de pacientes atendidos em um hospital de referência do estado do Pará - BATISTA, Lecildo Lira (Universidade Federal do Pará, 2017)
Penile neoplasms are a rare disease in developed nations and occur more in the development areas, which states as a major problem of public health by its mutilating features that may lead to social and psychological problems for the patient. The most important prognosis factor are the lymph node involvement and the presence of distance metastasis. Those patiens who have these features rarely survive for five years. By the other side, the prognosis is good at the initial phases and the cure is obtained in most of the cases. In the search for more reliable prognosis indicators, countless of gens and proteins associated with the penile carcinogenesis have been evaluated for a better understanding of the process, in order to achieve more accurate diagnosis methods to identify patients with aggressive disease, then submit them to a more efficient primarily treatment and a better survive rate. Some groups of epithelial and mesenchymal markers have been used to determinate the transition of mesenchymal epithelium in neoplasm tissues. Those groups include surface proteins like E-cadherin and cytoskeleton markers, as vimentin and β-catenin, and transcription factors, as Snail, Slug and Twist1. With this approach, we did a retrospective study which was analyzed 109 patients from Ophir Loyola Hospital, between January 2012 to November 2014. It was investigated the protein expression of Twist1, Kai1 and E-cadherin in penile tissues with benign and malign lesions to look for evidence of the immunoreactivity pattern and correlate that immunoreactivity pattern with the progression and invasion features of the penile neoplasms and other clinicopathological features of the studied tumor. In relation to E-cadherin, 48,6% of the patients had lower expression of this protein when compared to non-neoplasms tissues, this result showed statistical significance. But the association of the abnormal expression of E-cadherin with others clinicopathoogical factors was not found. The higher expression of Twist1 it was not associated with clinicopathological factors and the KAI1. There was statistical significance when we simultaneously compared the defective expression of E-cadherin and Kai1 and we obtained an inconclusive outcome about the association between them and there was not statistical significance among the analysis of the Twist1 e Kai1 proteins.